The Effect of Age, Ethnicity and Financial Expertise of Female Directors on Earnings Quality in Indonesia - Darmayanti, Yeasy; Azilah Husin, Nor; Azlina Md. Kassim, Aza; Suryadimal, Suryadimal (KnE Social Sciences, 2022)
‘Quality earnings’ are those that are free from accounting tricks and can be used to predict future conditions of the company. Some companies engage in downward manipulation of profits to reduce taxes, while other companies artificially increase profits to look better in the eyes of analysts and investors. Placing women on the board of directors to enhance supervision may reduce these activities and improve the quality of income. This study aimed to examine the effect of age, ethnicity, and financial expertise of female directors on earnings quality on the IDX for the period 2015 - 2018. The study found that (1) higher diversity in the age of female directors did not affect earnings quality; while (2) the more ethnically diverse, the lower the earnings quality. For the moderating variable of financial expertise, the results showed that the financial expertise of female directors weakened the relationship between diversity and earnings quality. Keywords: age diversity, ethnic diversity, financial expertise, earnings quality